A note on the term 'lithic' - George (Rip) Rapp (Journal of Lithic Studies, 2014)
The term ‘lithic’ is derived from the ancient Greek word for ‘rock’ (lithos), used in the late fourth century BCE by the scholar Theophrastus. The term ‘lithic’ in the way we use it today, meaning small rock artifact, most often chipped or ground stone, came into common use less than eight decades ago. The terms ‘stone tool’ and ‘stone implement’ remain firmly entrenched in the archaeological literature.